The Potential of Liquid for Breast Cancer: A Review - Panigoro, Sonar Soni; Yuella, Clarissa Kezia, - (UI Scholars Hub, 2022)
Introduction. Tissue biopsy is the current gold standard for cancer diagnosis, targeted treatment, and prognosis. However, biopsy is an invasive procedure that could result in postoperative bleeding, pain, and infection. Such limitations may now be resolved by the clinical technique known as liquid biopsy, which enables a better representation of disease status.Method. This literature review was conducted through online databases (PubMed, Ascopubs, EuroPMC) using the following keywords: